Non-Linear Socio-Cultural Strategies for Managing the Society’s Development: Problems of Conceptualisation in the Context of Cultural and Religious Diversity - Kovalenko, Yelena (Socio-Cultural Management Journal, 2024)
Introduction. The relevance of the study is due to the diversity of modern society and the complexity of conceptualising its management strategies. Purpose and methods. The purpose of the article is a philosophical analysis of non-linear concepts and strategies for managing the society’s development in the context of cultural and religious diversity. The methodological basis of the study is the dialectical principle of cognition, system-synergetic, historical, cultural, and interdisciplinary approaches to the study of the management laws of society development. Results. The essence of non-linear theory and strategy as an alternative expression of the universal pattern of society development is revealed. The article analyses the genesis of non-linear conceptions of society development in the pre-industrial period. Non-linear strategies of social development in the era of industrialism are considered. Non-linear strategies of social development at the stage of late industrialism are highlighted. The meaning of the socio-cultural identity strategies of societies is clarified. The strategies of the original development of society in the cultures of Islam, Buddhism and Hinduism are substantiated. The peculiarities of the original development strategy of society in the culture of Japanese Shinto Buddhism are revealed. Conclusions. The scientific novelty of the obtained results lies in deepening the theoretical foundations of non-linear strategic management of the development of societies of the Eastern and Middle Worlds, and their significance lies in supplementing science with new knowledge about non-linear strategies of development management in these societies.